1997
DOI: 10.1073/pnas.94.6.2472
|View full text |Cite
|
Sign up to set email alerts
|

Generation of NK1.1+T cell antigen receptor α/β+thymocytes associated with intact thymic structure

Abstract: following correction should be noted. On page 2475, the second line of the left column that reads ". . . were reconstituted with aly͞aly BM cells after lethal irradiation" should read ". . . were reconstituted with aly͞ϩ BM cells after lethal irradiation."Immunology. In the article "Modifying the sequence of an immunoglobulin V-gene alters the resulting pattern of hypermutation," by Beatriz Goyenechea and César Milstein, which appeared in number 24, November 26, 1996, of Proc. Natl. Acad. Sci. USA (93, 13979-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Thymic structure is disorganized in aly mice; the boundary of cortex and medulla is unclear (9,10), and ER-TR5-positive cells (medullary epithelial cells) are sparse (43). We also found that epithelial cells that bind the lectin UEA-1 (UEA-1 ϩ medullary epithelial cells) (44) were absent from the thymus of aly mice (our unpublished observation).…”
Section: Discussionmentioning
confidence: 66%
“…Thymic structure is disorganized in aly mice; the boundary of cortex and medulla is unclear (9,10), and ER-TR5-positive cells (medullary epithelial cells) are sparse (43). We also found that epithelial cells that bind the lectin UEA-1 (UEA-1 ϩ medullary epithelial cells) (44) were absent from the thymus of aly mice (our unpublished observation).…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, it has been shown that the NK1.1 ϩ ␣͞␤TCR ϩ thymocytes are not positively selected under the influence of thymic epithelial cells but are generated in the presence of CD4 ϩ 8 ϩ double positive thymocytes, which express nonpolymorphic major histocompatibility complex class I-like molecules, CD1 (2,(6)(7)(8)(9). This is so even though we recently have found that an intact microenvironment of the thymus makes up a component that is also important in generation of the NK1.1 ϩ ␣͞␤TCR ϩ thymocytes (10). In addition, Taniguchi et al (11) and Bendelac et al (12) reported that expression of an invariant TCR ␣ chain, V␣14-J␣281, is an essential requirement for development of (13,14).…”
Section: T Cells Of the I-mentioning
confidence: 81%
“…We and others have demonstrated that this is due to defective NF-B activation through the lymphotoxin (LT)-␤ receptor (LT␤R) (6,7,9), a receptor essential for the development of lymphoid organs (10). Thymic structure is also disorganized in NIK aly/aly mice, which is not observed in mice deficient for LT-␣ or LT-␤ (10); the medulla in NIK aly/aly mice is smaller than that in NIK aly/ϩ mice, and the boundary of the cortex and medulla is unclear (5,6,11). In addition to this abnormal lymphoid organogenesis, NIK aly/aly mice also serve as a model of autoimmune disease, but of unknown etiology (12); histopathological analysis of NIK aly/aly mice has revealed chronic inflammatory changes in several organs, including the liver, pancreas, lung, salivary gland, and lacrimal gland (Refs.…”
Section: Nf-b-inducing Kinase Establishes Self-tolerance In a Thymicmentioning
confidence: 99%